Hospitalization due to exacerbation of COPD: "Real-life" outcomes - Camargo,Lilia Azzi Collet da Rocha (2017)
Summary Introduction: Hospitalization due to chronic obstructive pulmonary disease exacerbation (eCOPD) may indicate worse prognosis. It is important to know the profile of hospitalized patients and their outcome of hospitalization to customize and optimize treatment. Method: Evaluation of patients hospitalized for eCOPD, with ≥ 10 pack/years and ≥ 1 previous spirometry with airway obstruction over the course of one year at the pulmonology service of a general hospital, applying: COPD assessment test (CAT); mMRc and Visual Analogue Scale (VAS) for dyspnea; hospitalized anxiety and depression questionnaire (HAD); Divo's comorbidities and Cote index; spirometry; and laboratory tests including number of eosinophils, C-reactive protein (CRP), brain natriuretic protein (BNP). Patient progression, number of days of hospitalization and hospitalization outcomes were observed. Results: There were 75 (12%) hospitalizations for eCOPD, with 27 readmissions, nine of which during a period ≤ 30 days after hospital discharge. The main outcomes were: number of days of hospitalization (17±16.5 [2-75]); hospital discharge (30 [62.5%] patients); discharge/rehospitalization (18 [37.5%] patients), eight of them more than once; death (7 [14.5%] patients), five during rehospitalization. We analyzed 48 patients in their first hospitalization. The sample comprised a heterogeneous group separated in three clusters according to age, FEV1, body mass index (BMI) and CAT. The clusters did not correlate with the main outcomes. Conclusion: Hospitalization for eCOPD is frequent. The number of readmissions was high and associated with death as an outcome. Patients hospitalized for eCOPD were a heterogeneous group separated in three clusters with different degrees of disease severity and no correlation with hospitalization outcomes.